S-BPM in the Wild: Practical Value Creation - Fleischmann, Albert; Schmidt, Werner; Stary, Christian (Springer Nature, 2015)
This is the first book to present field studies on the application of subject-oriented business process management (S-BPM). Each case presents a specific story and focuses on an essential modeling or implementation issue, and most end with implications or suggestions for further studies. Significant variables and success factors are identified that were discovered during the respective study and lead to suggesting S-BPM novelties. For each case, the authors explain step-by-step how the story develops, and provide readers guidance by detailing the respective rationale. The studies covered are clustered according to three main S-BPM themes: Part I “Business Operation Support” documents approaches to the practical development of S-BPM solutions in various application domains and organizational settings, while Part II “Consultancy and Education Support” highlights cases that can help to train readers in S-BPM modeling and knowledge acquisition for S-BPM lifecycle iterations. It also refers to architecting S-BPM solutions for application cases based on hands-on experience. Part III “Technical Execution Support” focuses on concepts for utilizing specific theories and technologies to execute S-BPM models. It also addresses how to create reference models for certain settings in the field. Lastly, the appendix covers all relevant aspects needed to grasp S-BPM modeling and apply it based on fundamental examples. Its format reconciles semantic precision with syntactic rigor.>Addressing the needs of developers, educators and practitioners, this book will help companies to learn from the experiences of first-time users and to develop systems that fit their business processes, explaining the latest key methodological and technological S-BPM developments in the fields of training, research and application.